THE INFLUENCE OF TRANSFORMATIONAL AND TRANSACTIONAL LEADERSHIP ON KNOWLEDGE SHARING: AN EMPIRICAL STUDY ON SMALL AND MEDIUM BUSINESSES IN INDONESIA - Ficke H. Rawung; Nikolas F. Wuryaningrat; Lenny E. Elvinita (Asian Academy of Management Journal, 2015)
Knowledge sharing plays an important role in knowledge management. Knowledge sharing intends to optimise knowledge sources. Optimum knowledge sources enable particular businesses to become more innovative. However, knowledge sharing is not an easy and simple process, and therefore, it requires another factor. The existence of leadership is expected to be a factor that solves this problem. The goal of this research is to analyse and identify the function of the transformational and transactional leadership that an owner or manager of a Medium-Scale Business Unit can use to encourage knowledge sharing. A survey was conducted on small- and medium-scale business production sectors in the North Sulawesi Province of East Indonesia. The data used in this research included 176 samples. The collected data were then analysed by using a variant-based structural equation model or Partially Least Square (PLS-SEM). The data analysis results provide empirical evidence that a transformational leadership style, particularly in the individual consideration and individual inspirational dimensions, positively impacts knowledge sharing activities. However, other dimensions, namely, intellectual stimulation and inspirational motivation, do not significantly encourage activities related to knowledge sharing. Moreover, transactional leadership on the contingent reward dimension does not significantly impact knowledge sharing.